Improving safety through statistical analysis of construction fatalities - Crewe, Adam; Agarwal, Jitendra; Chang, Yi Pin; ICASP14 (My University, 2023)
The construction industry has the highest rates of fatalities, disabilities, and injuries & illnesses among all industries. While this situation has improved in some countries, for example the UK, to achieve sustained improvements accident data must continue to be analysed. The purpose of this paper is to apply statistical analysis techniques to examine construction accident data thus leading to the identification of the contributory factors and associations among them to help improve safety. This study used data from the occupational construction fatality reports in Taiwan during 2013 and 2014. Descriptive statistical analysis showed that more than two thirds of the fatalities resulted from falls, slips and trips. The analysis also revealed that the employers perform poorly when installing and adopting Occupational Safety and Health (OSH) equipment and measures. Inferential statistical analysis, such as the Karl Pearsonﾒs Chi-square Tests, Association Strength and adjusted standardized residual analysis, enabled the identification of the contributing factors and their related subfactors with statistical significance. Amongst these, reinforce concrete building construction (project type), private project jurisdiction, scaffolds, staging and ladders (sources of injury), and unsafe conditions such as no guardrails, covers, or/and safety nets, were found to be the prominent factors. These factors were also found to have relatively strong association with each other on the occurrence of fatal accidents. Construction stakeholders and OSH authorities should take note of these to make decisions and/or develop accident prevention strategies.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED